Paternal Smoking and Risk of Childhood Acute Lymphoblastic Leukemia: Systematic Review and Meta-Analysis. (29th May 2011) - Liu, Ruiling; Zhang, Luoping; McHale, Cliona M.; Hammond, S. Katharine
Abstract : Objective . To investigate the association between paternal smoking and childhood acute lymphoblastic leukemia (ALL). Method . We identified 18 published epidemiologic studies that reported data on both paternal smoking and childhood ALL risk. We performed a meta-analysis and analyzed dose-response relationships on ALL risk for smoking during preconception, during pregnancy, after birth, and ever smoking. Results . The summary odds ratio (OR) of childhood ALL associated with paternal smoking was 1.11 (95% Confidence Interval (CI): 1.05–1.18, I 2 = 18 %) during any time period, 1.25 (95% CI: 1.08–1.46, I 2 = 53 %) preconception; 1.24 (95% CI: 1.07–1.43, I 2 = 54 %) during pregnancy, and 1.24 (95% CI: 0.96–1.60, I 2 = 64 %) after birth, with a dose-response relationship between childhood ALL and paternal smoking preconception or after birth. Conclusion . The evidence supports a positive association between childhood ALL and paternal ever smoking and at each exposure time period examined. Future epidemiologic studies should assess paternal smoking during well-defined exposure windows and should include biomarkers to assess smoking exposure and toxicological mechanisms.